Climate change implications for the public finances and fiscal policy: An agenda for future research and filling the gaps in scholarly work. Editorial - Luiz de Mello; Jorge Martinez-Vazquez (Economics: The Open-Access, Open-Assessment Journal, 2022)
Climate change will pose a major challenge for humanity in future decades. Central to the policy debate are its implications for the public finances and the conduct of fiscal policy more generally. This editorial outlines the budgetary effects, the regulatory and standard-setting challenges, internal governmental organisational changes, and the resource reallocation implications of policies to control climate change and their efficient implementation. The scope for further work - both theoretical and empirical - to bridge existing gaps in the related economics literature is then discussed. Finally, the editorial outlines research questions and first steps on an agenda for policy-relevant research.
Keywords: 330; climate change; fiscal policy; inter-governmental coordination; methodology; regulation; research agenda; resources